Impact of the 2008 economic crisis on the US economy - Poleno, Kirill (2023)
This bachelor thesis is aimed at examining the impact of the 2008 economic crisis on the US economy. There are three main chapters in my thesis. The first chapter gives an overview of the causes of the 2008 financial crisis, which broke out in the US and then spread around the world. Both the preconditions for the financial crisis that emerged in the housing market and the role of the government and the federal reserve system in these events are examined based on the data collected. The second part of my paper looks at the impact of the crisis. In the first subchapter, the effects of the crisis on the economic development of the United States are analysed by examining some indicators. The effects of the crisis on inflows, outflows, and stock of foreign direct investment in the USA are discussed in the second subchapter. In the third subchapter, the impact of the crisis on foreign trade in the USA is analysed based on the collected data. The final part of my paper analyses the effect of the government's responses to this financial crisis based on the relevant data obtained through data research methods. The first subchapter analyses government fiscal policy based on acts adopted by the US Congress between 2008 and 2010. The second chapter focuses on the measures taken by the Federal Reserve System in response to the crisis on the basis of the data available.